1996
DOI: 10.1111/j.1365-3180.1996.tb01666.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic joint action of MCPA ester and metsulfuron‐methyl

Abstract: SaminaTyMCPA is antagonistic to a range of herbicides but there is limited research on its compatibility with other broad-leaved weed herbicides. In this study we assessed the joint action of MCPA ester and metsulfuron-methy! on Brassica napus L, using the additive dose model (ADM). The fresh weight responses for selected ratios of the mixture were plotted on the ADM and compared to the predicted mixture response at three assessment levels -50, 75 and 90% control. The mixture demonstrated increasing synergism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Previous studies with mixtures of glyphosate and diverse groups of herbicides have revealed antagonism on annual and perennial weed species (Stahlman & Philips, 1979; O'Sullivan & O'Donovan, 1980a,b; Selleck & Baird, 1981). Joint action studies with sulfonylurea herbicides have involved phenoxyalkanoic acid herbicides (Mathiassen & Kudsk, 1993; Kudsk & Mathiassen, 1995; Hollaway et al. , 1996; Streibig et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with mixtures of glyphosate and diverse groups of herbicides have revealed antagonism on annual and perennial weed species (Stahlman & Philips, 1979; O'Sullivan & O'Donovan, 1980a,b; Selleck & Baird, 1981). Joint action studies with sulfonylurea herbicides have involved phenoxyalkanoic acid herbicides (Mathiassen & Kudsk, 1993; Kudsk & Mathiassen, 1995; Hollaway et al. , 1996; Streibig et al.…”
Section: Discussionmentioning
confidence: 99%
“…Strong antagonism has been demonstrated with mixtures of the dimethylamine salt of MCPA and chlorsulfuron or metsulfuron-methyl. 22 Kudsk and Mathiassen,17 however, found that mixtures of mecoprop ethylene glycol diester and tribenuron-methyl followed ADM and Hollaway et al 23 found synergistic e †ects with MCPA iso-octyl ester and sulfonylureas at and response levels. At level there ED 75 ED 90 ED 50 was a tendency for the observed values to show a somewhat similar pattern to the one observed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, herbicide formulation can lead to increasing or decreasing efficacy of herbicides in a mixture rather than predicted by ADM. For example, Streibig, Kudsk and Jensen (1998) showed that mixing mecoprop-P potassium salt with MCPA dimethylamine salt made the mixture additive under the ADM, while mixing the same herbicides as esters made the mixtures synergistic under ADM. In another experiment, Hollaway, Hallam and Flynn (1996) found synergistic effects with MCPA isooctyl ester and metsulfuron-methyl at ED 75 and ED 90 response levels on oilseed rape [Brassica Table 5. Dose-response parameters of the log-logistic model for either the herbicides applied alone or fixed-ratio binary mixtures of foramsulfuron or nicosulfuron with 2,4-D plus MCPA on redroot pigweed and common lambsquarters at the 4-6-true leaf stage.…”
Section: Discussionmentioning
confidence: 99%